Cultural Baggage: Do Immigrants Import Corruption?. (5th February 2019) - Bologna Pavlik, Jamie; Lujan Padilla, Estefania; Powell, Benjamin
Abstract : Do immigrants undermine culture in a way that destroys productivity in destination countries? Some scholars have argued that because immigrants come from countries with dysfunctional social capital—norms and institutions—they will import it and pollute the social capital in destination countries. One potential channel through which this could occur is corruption. We examine stocks and flows of immigrants over a 20‐year time period to see if corruption increased in destination countries. We generally find that immigration is not associated with increases in corruption. Additionally, we find that immigration tends to decrease corruption in destination countries with low levels of corruption or high levels of economic freedom.